Growth performance and survival rate of planted dipterocarp on different planting techniques; mono and mixed species at Gunung Apeng Forest Reserve - Siti Asmah, binti Hameed Sultan (Universiti Malaysia Sarawak (UNIMAS), 2015)
A study was conducted in order to assess the growth performance and survival rate of planted dipterocarp species under different planting technique; mono and mixed planting technique at Gunung Apeng Forest Reserve, Serian, Sarawak. The objectives of this study were to evaluate the growth performance and survival rate and to identify the better tree planting technique of planted dipterocarp in different planting technique for purposes of reforestation in tropical region. The study was established on reforestation site, mono species plot (MN2011 and MN2014) planted with Dryobalanops beccarii and mixed species plot (MX2011 and MX2012) planted Dryobalanops beccarii and other dipterocarp species. The growth performance at different planting techniques was evaluated by obtained the measurement of diameter, height, light intensity within trees and survival rate. The finding indicated that the mean annual increment in diameter (MAID) in MX2012 was the highest compared to MN2011, MX2011 and MX2014. Meanwhile, for mean annual increment in height (MAIH) in MN2014 was the highest compared to other plots. The survival rate of planted dipterocarp of MN2011, MN2014, MX2011 and MX2012 were 83%, 91%, 91% and 84% respectively. The growth performance and survival rate of planted dipterocarp species highly influence by light intensity, microclimate, topography, and competition. In conclusion, mono species planting technique provides a better survival rate and mixed species planting technique better growth performance for planted dipterocarp trees. Therefore, this proved that both planting techniques; mono and mixed species are suitable for dipterocarp species reforestation activity in Sarawak. As a recommendation, to prevent competition between planted dipterocarp and pioneer species such as shrubs, maintenance such silvicultural practise is very crucial in reforestation site.